2022
DOI: 10.1515/pr-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

Refusing invitations and offers in second language Chinese: effect of proficiency at the actional and interactional levels

Abstract: The present study investigates the role of proficiency in the development of second language (L2) Chinese learners’ ability to negotiate refusals of invitations and offers in conversational interactions. Fifty-four American English learners of L2 Mandarin Chinese at three proficiency levels, and 22 native speakers, completed a four-item naturalized roleplay task. Findings suggest positive effects of proficiency on L1 American English L2 Chinese learners’ production of refusals at both actional and interactiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…First, based on a thorough review of the literature, the first author decided on the following three dimensions of pragmatic performance for scoring: Content Delivery (sociopragmatics), Language Use (pragmalinguistics), and Discourse Control (interactional features), consistent with an interactional perspective of pragmatic competence. The first author then devised descriptors of each criterion drawing on previous L1 and L2 Mandarin refusal interaction research (Su, 2020(Su, , 2021(Su, , 2022. Content Delivery evaluates whether speakers can realize the intended speech act, in this case, refusals, with sufficient justification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, based on a thorough review of the literature, the first author decided on the following three dimensions of pragmatic performance for scoring: Content Delivery (sociopragmatics), Language Use (pragmalinguistics), and Discourse Control (interactional features), consistent with an interactional perspective of pragmatic competence. The first author then devised descriptors of each criterion drawing on previous L1 and L2 Mandarin refusal interaction research (Su, 2020(Su, , 2021(Su, , 2022. Content Delivery evaluates whether speakers can realize the intended speech act, in this case, refusals, with sufficient justification.…”
Section: Methodsmentioning
confidence: 99%
“…After outlining the criteria and major descriptors, the first author drafted the pilot HB scale based on the transcribed roleplay performance of learners in this study (the same dataset as in Su, 2022) and 22 native speakers in an earlier study (Su, 2020). Using the pilot HB scale, the first author, an experienced college Chinese as a foreign language (CFL) instructor, and her research assistant, a Chinese MA pedagogy student with 6 years of CFL teaching experience in both public school and college settings, rated the audio-recorded roleplays of 11 learners (five second-year, four third-year, and two fourth-year), amounting to 55 roleplay conversations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, research on L2 pragmatics in Chinese started late, but the number of studies in Chinese is increasing rapidly. Previous L2 pragmatics research in Chinese has investigated speech acts such as requests (e.g., Li et al., 2021; Ren, 2019; Su & Ren, 2017), apologies (e.g., Yang & Ke, 2021), refusals (e.g., Su, 2022), compliment responses (e.g., Jin, 2012; Tang et al., 2021), greeting responses (e.g., Ying & Ren, 2022), formulaic expressions (e.g., Taguchi et al., 2013; Wang & Halenko, 2019), and pragmatic markers (e.g., Diao, 2016; Ren, 2022a). Studies have shown that learners’ pragmatic development often follows a non‐linear trajectory, which is influenced by a number of factors including L2 proficiency, study abroad length, availability of pragmatic targets, and learners’ pragmatic agency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The influence of L2 proficiency is an often-examined topic. For instance, Su (2022) explored the effect of proficiency on the development of L2 Chinese learners' refusals of invitations and offers through a roleplay task. The results suggested that the learners' proficiency level had a positive effect on their refusal production and their acquisition of the sequential organization of refusals.…”
Section: L2 Pragmatics In Chinesementioning
confidence: 99%